Benefits and costs of ecological restoration: Rapid assessment of changing ecosystem service values at a U.K. wetland. Issue 20 (23rd September 2014) - Peh, Kelvin S.‐H.; Balmford, Andrew; Field, Rob H.; Lamb, Anthony; Birch, Jennifer C.; Bradbury, Richard B.; Brown, Claire; Butchart, Stuart H. M.; Lester, Martin; Morrison, Ross; Sedgwick, Isabel; Soans, Chris; et al.
Abstract Restoration of degraded land is recognized by the international community as an important way of enhancing both biodiversity and ecosystem services, but more information is needed about its costs and benefits. In Cambridgeshire, U.K., a long‐term initiative to convert drained, intensively farmed arable land to a wetland habitat mosaic is driven by a desire both to prevent biodiversity loss from the nationally important Wicken Fen National Nature Reserve (Wicken Fen NNR) and to increase the provision of ecosystem services. We evaluated the changes in ecosystem service delivery resulting from this land conversion, using a new Toolkit for Ecosystem Service Site‐based Assessment (TESSA) to estimate biophysical and monetary values of ecosystem services provided by the restored wetland mosaic compared with the former arable land. Overall results suggest that restoration is associated with a net gain to society as a whole of $199 ha−1y−1, for a one‐off investment in restoration of $2320 ha−1. Restoration has led to an estimated loss of arable production of $2040 ha−1y−1, but estimated gains of $671 ha−1y−1 in nature‐based recreation, $120 ha−1y−1 from grazing, $48 ha−1y−1 from flood protection, and a reduction in greenhouse gas (GHG) emissions worth an estimated $72 ha−1y−1. Management costs have also declined by an estimated $1325 ha−1y−1. Despite uncertainties associated with all measured values and the conservative assumptions used, we conclude that there was a substantial gain to society as a whole from this land‐use conversion. The beneficiaries also changed from local arable farmers under arable production to graziers, countryside users from towns and villages, and the global community, under restoration. We emphasize that the values reported here are not necessarily transferable to other sites.